Optimal management of RA patients who require Biologic Therapy (ORBIT) – a randomised controlled, non-inferiority study - Porter, D; van Melckebeke, J; Dale, J; Messow, C; McConnachie, P; Walker, A; Munro, R; McLaren, J; McRorie, E; Packham, J; Buckley, C; Harvie, J; et al. (Elsevier, 2016)
Background Tumour necrosis factor inhibition (TNFi) and B cell depletion are highly effective treatments for active rheumatoid arthritis (RA) but to date no randomised controlled trials have directly compared their safety, efficacy and cost effectiveness. This study was undertaken to test the hypothesis that using rituximab would be clinically non-inferior and cheaper compared to TNFi therapy in biologic-naive patients with RA. Methods An open label randomised controlled trial of two strategies of treatment over 12 months in patients with active, sero-positive RA and an inadequate response to synthetic disease modifying anti-rheumatic drugs (DMARDs). Patients were randomised (1:1) to receive either rituximab or TNFi (either etanercept or adalimumab) as their first biologic DMARD. Patients switched treatment to the alternative mode of action biologic in the event of drug-related toxicity or lack/loss of response. The primary outcome measure was the change in 28 joint count disease activity score (DAS28-ESR) between 0 and 12 months. The non-inferiority margin was specified as 0.6 DAS28-ESR units. Findings 295 patients were randomised and treated with either rituximab or TNFi therapy. At baseline, there were no significant differences between the groups in age, gender, disease duration, disease activity or intolerance to methotrexate. After 12 months, the change in DAS28-ESR for patients randomised to rituximab-first (-2.7) was non-inferior to that for patients randomised to TNFi-first (-2.6) with the difference lying within the pre-specified non-inferiority limit of 0.6 units (estimated difference -0.19, 95% CI -0.51, 0.13; p=0.24). No between-group differences were found for the proportion of patients achieving good response (rituximab 43% v TNFi 40%), DAS28-ESR remission (rituximab 23% v TNFi 21%), ACR20 (rituximab 66% v TNFi 71%), ACR50 (rituximab 49% v TNFi 45%) or ACR70 (rituximab 25% v TNFi 23%) response. There were no differences in the change in health assessment questionnaire (HAQ) score, Hospital Anxiety and Depression (HAD) score or health-related quality of life. A higher proportion of patients switched from TNFi therapy to rituximab than vice versa (rituximab 19% v TNFi 32.5%, p=0.008). The health related costs associated with the rituximab-first strategy were lower than the TNFi-first strategy (£8391 v £10,356 per patient, p<0.001). In summary, starting treatment with rituximab is non-inferior to initial TNFi therapy in biologic-naïve patients with sero-positive RA, and is cost saving over 12 months.